Feasibility Analysis of the Construction of the North Surabaya Hospital from the Financial Aspect - Wahyu, Lestyanto; Patriadi, Andi; Sajiyo, Sajiyo (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
The purpose of this research is to analyze the investment feasibility of North Surabaya Hospital, Bulak District, Surabaya City with the parameters of Net Present Value, Internal Rate of Return, Benefit Cost Ratio (BCR) and Payback Period. This research focuses on the North Surabaya Hospital which was built by the Surabaya City Government Health Office with a budget allocation for the 2026 fiscal year. The research instruments used are interview guidelines and observation sheets, with data collection procedures through interviews with related parties in hospital construction, site observation, and documentation which includes primary and secondary data. Based on the investment analysis of North Surabaya Hospital and sensitivity evaluation of operational costs and potential income, the conclusions obtained are: Alternative 1 is feasible because it produces an NPV value of Rp. 211,014,227,005, IRR of 9.85%, BCR of 1.23 and PP of 7.69 years. Alternative 2 is not feasible because it generates NPV of IDR 28,416,192,984, IRR of 6.57%, BCR of 1.14 and PP of 8.34 years. Alternative 3 is not feasible because it generates NPV of IDR 66,444,241,124, IRR of 7.30%, BCR of 1.16 and PP of 8.20 years. Alternative 4 is feasible because it generates NPV of Rp. 166,294,504,181, IRR of 9.26%, BCR of 1.20 and PP of 7.70 years.